(untitled) (Journal of Pathology of Nepal, 2018)
Adrenal angiomyolipoma is a rare benign entity and only to sixteen cases have been reported in English literature till date. Other site of occurrence is liver, spleen, lungs, bone and ovary. We report a female aged 54 years, who presented with left flank pain, on CT scan showed left adrenal mass. Patient underwent laparoscopic adrenalectomy and final histopathological examination revealed angiomyolipoma of left adrenal gland.